AL ZARNUJI AND INSTRUCTIONAL IMPACT (International Conference on Social and Islamic Studies, 2021)
Al Zarnuji offers an educational concept that concentrates on learning by doing. Like the times, Islamic education in particular is also more flexible. No longer using traditional methods alone. In addition, he taught that education is not just a transfer of knowledgeand skills, but the most important thing is the transfer of moral values. The moral values taught are moral values, both physical and spiritual. This article describes how the concept of Al Zarnuji's education has an impact on the learning process at school. This article was written using a qualitative approach with a case study type. Al Zarnuji's educational concept has an impact on the development of 3 character values in the school curriculum.The discussion ended with the recommendation of teachers in Islamic educational institutions to dig deeper into Al Zarnuji's thoughts to be implemented in the learning process.